RANCANG BANGUN CONVERTER KIT SEBAGAI ALAT KONVERSI ENERGI SEPEDA MOTOR 100cc BERBAHAN BAKAR GAS LPG - Rizal Justian Setiawan; Muhammad Sahid Fitrihartanta; Mujiono Mujiono; Didik Nurhadiyanto (Politeknik Negeri Ketapang, 2021)
LPG is one of the Gas Fuel products that can be used as fuel to replace the use of Oil Fuel. Therefore, an energy conversion tool is needed to utilize LPG as a motorcycle energy source. The purpose of this research is to design and manufacture a gas motor converter kit. This converter kit has three technologies, such as a fuel distribution system using a manual fuel faucet, a solenoid valve that functions to cut off gas flow, and the position of the fuel tube under the seat. The research method using VDI2221 (Verein Deutcher Ingenieure). The research result is the creation of converter kits that are made through the design, turning, milling, welding, and assembling process. The research conclusion is the converter kits can be implemented on 100cc motorcycles, and no leaks or defects were found in the converter kits, so the tool can be used properly on motorcycles.